A nuclear-encoded function essential for translation of the chloroplast psaB mRNA in chlamydomonas. - Stampacchia, O (1997)
We report the analysis of a photosystem I-deficient mutant of Chlamydomonas reinhardtii, F15, that contains a mutation at the TAB1 (for translation of psaB mRNA) nuclear locus. Pulse labeling of chloroplast proteins revealed that the synthesis of the two photosystem I reaction center polypeptides PSAA and PSAB was undetectable in this mutant. The mRNA levels of these proteins were only moderately reduced, suggesting that the primary defect occurs at a step during or after translation. We constructed chimeric genes consisting of the psaA and psaB 5' untranslated region (5' UTR) fused to the aminoglycoside adenyltransferase (aadA) coding sequence, which confers spectinomycin resistance. Insertion of these genes into the chloroplast genome through biolistic transformation and analysis of their expression in the TAB1 mutant nuclear background revealed that the psaB (but not the psaA) 5' UTR is the target of the wild-type TAB1 function. This suggests that TAB1 is required for the initiation of psaB mRNA translation. The dependence of PSAA synthesis or accumulation on PSAB synthesis is strongly suggested by the identification of a suppressor mutation within the psaB 5' UTR. The suppressor specifically restores the synthesis of both proteins in the presence of the tab1-F15 mutation. The location of the suppressor mutation within a putative base-paired region near the psaB initiation codon suggests a role for TAB1 in the activation of translation of the psaB mRNA.